Serapan Phospat dan Pertumbuhan Bibit Kelapa Sawit pada Tanah Ultisol Akibat Cendawan Mikoriza Abuskula - Made Same (Jurnal Penelitian Pertanian Terapan, 2011)
One of the disadvantages of oil palm development is the limitedness of fertile soil. A constraint faced by both big plantation and small holders is the high cost of crop maintenance. Around 60% of the total crop maintenance is used for fertilizing the crop. This study aims at finding out phosphate absorbtion and the growth of oil palm seedling with the addition of Arbuscullar Mycorrhizal Fungi (AMF) and different dosages of phosphate fertilizer. A factorial Complete Randomized Design with three replications has been used. The first factor was the addition of AMF consisting of three levels: M0=0 g AMF polybag-1, M1=5 g AMF polybag -1, and M2 = 10 g AMF polybag -1. The second factor was the addition of four levels of phosphate using TCP-36: P0= 0 g TCP-36 polybag-1, P =15 g TCP-36 polybag-1, P2=30 g TCP-36 polybag-1, and P3=45 g TCP-36 polybag-1. Results showed that the Application of 10 g AMF polybag-1was able to increase P-absorbtion and the growth of oil palm seeding such as fresh crown weight, dry crown weight, fresh root weight, dry and root weight. Application of 45 g TCP-36 polybag -1was able to increase the growth such as plant height, dry crown weight, fresh root weight, and dry root weight. Keywords: Arbuscullar Mycorrhizal Fungi, phosphate, and oil palm